UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK TOPIK LINGKARAN MELALUI PEMBELAJARAN THINK PAIR SHARE BAGI SISWA KELAS VIII SMP NEGERI 1 GARUT - Suhartini; Abdul Aziz; Hayat Nandang Kurnia (Jurnal Ilmu Pendidikan dan Sosial, 2022)
This classroom action research which consists of three cycles aims to determine the increase in the mathematical problem solving ability (KPMM) of students whose learning uses the Think-Pair Share (TPS) type cooperative strategy. In addition, this study also aims to determine students' attitudes towards mathematics (SSTM) and learning completeness. The research subjects in this study were class VIII-A students of SMP Negeri 1 Garut. The instruments used consisted of: the early knowledge test of mathematics (PAM), the KPMM test, the SSTM scale based on the Likert scale, as well as observation sheets of teacher and student activities. The instrument was declared to have met the requirements for face and content validity. Data analysis was carried out with an increase test (normalized gain), learning completeness and the average level of mastery. The main results of this study are as follows; (1) TPS learning by "students working on LKS in groups" can increase the KPMM of students from PAM with moderate criteria. (2) TPS learning by "students in groups working on LKS and Question Cards" can increase the KPMM of students from PAM with medium criteria, (3) TPS learning by "students working in groups on LKS and guided by the teacher how to change story questions into the form of a mathematical model” can increase the KPMM of students from PAM with high criteria. The number of students who complete in cycle III is more than the number of students who complete in cycles I and II. Students' attitudes towards mathematics after learning TPS are in the moderate attitude classification.